Influencia del trabajo en equipo como estrategia en el análisis-crítico de la historia y cultura del Perú, en los estudiantes del primer año de la especialidad de historia y geografía, facultad de educación y ciencias de la comunicación, de la Universidad Nacional de Trujillo - Vaca Rosado, Jaime Milton (2016)
This study was conducted in order to determine the extent to teamwork and strategy significantly influences-critical analysis of the history and culture of Peru, in the first year students of the specialty of History and Geography, Faculty of Education and Communication Sciences, National University of Trujillo-2014. The research was carried out with a study population of 131 students and the sample consisted of 59 students; 28 in the experimental group and 31 in the control group; which have similar age and characteristics. The experimental method was used in its execution, to determine in the experimental group the influence of History-critical analysis and Culture in Peru, students investigated. The analysis of the results has shown that teamwork and strategy significantly influences-critical analysis of history and culture of Peru, where freshmen specialty of History and Geography, investigated.